Linkage group selection: Rapid gene discovery in malaria parasites - Culleton, Richard; Martinelli, Axel; Hunt, Paul; Carter, Richard (Genome Research, 2005)
The identification of parasite genes controlling phenotypes such as drug resistance, virulence, immunogenicity, and transmission is vital to malaria research. Classical genetic methods have achieved these goals only rarely and with difficulty. We describe here a novel genetic method, Linkage Group Selection (LGS), which achieves rapid de novo location of genes encoding selectable phenotypes of malaria parasites. A phenotype-specific selection pressure is applied to the uncloned progeny of a genetic cross between two malaria parasites that differ in the relevant phenotype. Selected and unselected progeny are analyzed using genome-wide quantitative genetic markers. Markers of the “sensitive” parent, which are reduced after selection, are sequenced and located in genomic databases. They are expected to be closely linked to gene(s) determining the phenotype under selection. We have validated LGS with the rodent malaria parasite Plasmodium chabaudi chabaudi using a phenotype, pyrimethamine resistance, whose controlling gene, that encoding dihydrofolate reductase (dhfr), is known. We show that molecular markers closely linked to dhfr, and only those linked to this gene, were reduced or removed by pyrimethamine treatment in accordance with the expectations of LGS.